Deploying IPv6 in broadband access networks - Ahmed, Adeel; Asadullah, Salman; Safari eBooks (Hoboken, N.J. : Wiley, 2009)
"With the exponential growth of the Internet and increasing number of end users, service providers are increasingly looking for ways to expand their networks to meet the scalability requirements of the growing number of Internet-ready appliances or "always-on" devices. This book bridges a gap in the literature by providing coverage of Internet Protocol Version 6 (IPv6), specifically in broadband access networks. The authors, who are Cisco Certified Internetworking Experts (CCIE), provide comprehensive and first-rate coverage. The authors also discuss challenges faced by service providers and how IPv6 addresses these issues. Additionally, the book is complemented with examples throughout to further facilitate readers' comprehension and a real large-scale IPv6 BB SP case study is presented. Deploying IPv6 in Broadband Access Networks is essential reading for network operators, network design engineers and consultants, network architects, and members of the networking community"--Resource description page.
IPv6 drivers in broadband networks -- IPv6 overview -- Deploying IPv6 in cable networks -- IPv6 deployment in DSL, ETTH, and wireless networks -- Configuring and troubleshooting IPv6 on gateway routers and hosts -- Configuring and troubleshooting IPv6 on edge routers -- Configuring and troubleshooting IPv6 on provisioning servers -- Appendix A : IPv6 case study -- Appendix B : DHCPv6 message types and option codes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: TCP/IP (Computer network protocol); Broadband communication systems; Electronic books